Inca gold - Cussler, Clive (London : Harper Collins, 1994)
When Dirk Pitt saves a group of archaologist from drawing, he finds himself caught up in a smuggling ring searching for lost Inca treasure.
Keywords: Incas-Antiqquities -- Fiction; Pitt, Dirk (Fictitiaus Character). -- Fiction